2007
DOI: 10.1111/j.1471-6712.2007.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and coercion among voluntary, persuaded/pressured and committed patients in acute psychiatric treatment

Abstract: The data were limited to the patients' subjective reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 17 publications
1
29
0
1
Order By: Relevance
“…Additionally, satisfaction appeared to be negatively associated with residing on a closed ward and experiencing coercion. Several studies proposed a link between these factors (Greenwood et al, 1999;Smith et al, 2014;Sorgaard, 2007). Experiences of coercion are more common in those who are admitted involuntarily (Fiorillo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, satisfaction appeared to be negatively associated with residing on a closed ward and experiencing coercion. Several studies proposed a link between these factors (Greenwood et al, 1999;Smith et al, 2014;Sorgaard, 2007). Experiences of coercion are more common in those who are admitted involuntarily (Fiorillo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative non-randomised papers (Kohler et al, 2015;Muller et al, 2002;Shiva et al, 2009;Sorgaard, 2007) showed a good level of quality, with all four scoring 75%, although some studies reported a low response rate. Of the quantitative descriptive papers reviewed, nine scored 25% (Berghofer et al, 2001;Brunero et al, 2009;Cleary et al, 2009;Gebhardt et al, 2013;Kelstrup et al, 1993;Middelboe et al, 2001;Prince, 2006;Ruggeri et al, 2003;Soergaard et al, 2008), seven scored 50% (Alexius et al, 2000;Barker et al, 1996;Boydell et al, 2012;Gigantesco et al, 2002;Gjerden, 1997;Howard et al, 2003;Smith et al, 2014;Zendjidjian et al, 2014) and three scored 75% (Kuosmanen et al, 2006;Olusina et al, 2002;Zahid et al, 2010).…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Admissions formally defined as voluntary are often the outcome of a complex process involving advice, persuasion, pressure and threats from patients' families or professionals (Kjellin et al, 2004). Hence, the legal status of admission is only a crude proxy for experienced coercion and many 'voluntary' patients feel excluded from treatment decisions and psychologically forced into hospitalisation (Sorgaard, 2007;Bindman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Four studies have identified interactive processes, broadly related to 'being heard' that are important in the patients' experience of coercion. 23,[27][28][29] Using different measures, these studies all show that patients' who experienced professional staff as listening to their views as feeling less coerced, even if involved in legally mandated treatment. Qualitative research mirrors this finding.…”
Section: Who Experiences Coercion Most?mentioning
confidence: 99%